6(1+c)=5(c-5)

Simple and best practice solution for 6(1+c)=5(c-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(1+c)=5(c-5) equation:


Simplifying
6(1 + c) = 5(c + -5)
(1 * 6 + c * 6) = 5(c + -5)
(6 + 6c) = 5(c + -5)

Reorder the terms:
6 + 6c = 5(-5 + c)
6 + 6c = (-5 * 5 + c * 5)
6 + 6c = (-25 + 5c)

Solving
6 + 6c = -25 + 5c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-5c' to each side of the equation.
6 + 6c + -5c = -25 + 5c + -5c

Combine like terms: 6c + -5c = 1c
6 + 1c = -25 + 5c + -5c

Combine like terms: 5c + -5c = 0
6 + 1c = -25 + 0
6 + 1c = -25

Add '-6' to each side of the equation.
6 + -6 + 1c = -25 + -6

Combine like terms: 6 + -6 = 0
0 + 1c = -25 + -6
1c = -25 + -6

Combine like terms: -25 + -6 = -31
1c = -31

Divide each side by '1'.
c = -31

Simplifying
c = -31

See similar equations:

| 7.5=2x-1.5 | | 1+4x=5-6x | | 3x+38=8x+5 | | 2/5+1/3-13/15 | | 8x^2=-4x-5 | | 0.1x+0.05y+5y=100 | | 6x-5/3x | | 3x-2x-8=0 | | -1/5-7/10 | | 5n+7=57 | | -9m-(4+3m)=-(2m-1)-5 | | -x^2+11x+80=0 | | s/8=2 | | u/2=3 | | x^2-10x-96=0 | | -7/2-(5/8+1/4)= | | (13x+5y)(13x-5y)= | | 22x-11y=33 | | 9(7p-6)=2 | | x+x+(x-200)=1030 | | -x^2-25x-66=0 | | 54/5/15/7 | | (5+11x)(7+6x)= | | x-(8)=16 | | 2x+x=1030 | | -7+(-4)-(-21)= | | 2x+x-170=1200 | | lm(2m+3)=8 | | 2x+y=1030 | | 5x+12y-9=0 | | (-22)+15-(-7)-4= | | (5n-1)(n-1)=0 |

Equations solver categories